Evaluasi Screening Dokumen Verifikasi Internal dalam Menentukan Kodingan di Era BPJS - Tri Jenny Minarsih; Doni Jepisah; Nofiyadi Nofiyadi (Faculty of Social Science, Universitas Negeri Padang, 2025)
The completeness of medical record documents is a critical factor in the internal verification of BPJS Kesehatan claims and the determination of INA-CBGs coding. Incomplete documentation may hinder the coding process, increase the number of pending claims, and delay claim submission, ultimately affecting hospital cash flow. This study aimed to analyze the level of completeness of medical record documents in the BPJS claim verification process at RS Mesra, identify key problems and contributing factors, and formulate solutions along with an improvement intervention plan. This study employed a qualitative approach with a case study design, using direct observation and document review of BPJS claims in the Casemix Unit and Medical Records Unit of RS Mesra. Problem identification was conducted using the Urgency, Seriousness, and Growth (USG) method, while root cause analysis was performed using Fishbone Analysis. A Plan of Action (PoA) was subsequently developed as a system improvement intervention. The findings revealed that the completeness of medical record documents at the internal verification stage remained low. Essential documents, including medical resumes, supporting examination results, treatment summaries, and medication usage logs, were frequently incomplete. The main issues identified included inaccurate ICD-10 diagnosis documentation, the absence of Service Level Agreements (SLA) and Standard Operating Procedures (SOP) for document screening, ineffective inter-unit coordination, and limited functionality of the Hospital Information System (SIMRS) in automatically verifying document completeness. These systemic problems directly contributed to the increasing number of pending BPJS claims. In conclusion, improving medical record completeness requires an integrated approach involving enhancement of human resource competencies, strengthening internal regulations, optimization of SIMRS, and improved inter-unit coordination to support effective BPJS claim management at RS Mesra.